Researching the powerful: Seeking knowledge about policy - Ozga, J (2011)
This article introduces the articles in the collection on 'Researching the Powerful' by providing some background on the project 'Knowledge and Policy' which gave rise to the research on which the articles are based. It also offers some reflections on the 'work of construction' of research, with particular attention to the ways in which policy elites, which are the main focus of the research processes described and discussed in the articles that follow, seek to control, manipulate and manage the research process. This article draws attention to a finding reported in many of the articles in this special edition - namely, that this work of construction that policy makers do becomes in itself a source of knowledge about policy.